2003
DOI: 10.1152/ajpregu.00030.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increased connexin43-mediated intercellular communication in a rat model of bladder overactivity in vivo

Abstract: Bladder overactivity associated with outflow obstruction is a common human condition recapitulated in the female rat by narrowing the diameter of the urethra. The goal of these studies was to evaluate the role of intercellular communication through connexin43 (Cx43)-derived gap junction channels to bladder overactivity following partial urethral outflow obstruction of 3-day to 6-wk duration. Cx43 mRNA and protein expression were barely detectable by Northern or Western blots, respectively, in the detrusor laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 35 publications
5
111
1
1
Order By: Relevance
“…Cx43 is a biogenetic precursor of gap junctions, which are the main connexons expressed in astrocytes (11)(12)(13). It has been reported that Cx43 hemichannels are sensitive to various stimuli, including osmotic stimulation (19). A connexin hemichannel spans unopposed plasma membrane regions and, following docking with partners, produces a gap junction channel that allows for direct intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is a biogenetic precursor of gap junctions, which are the main connexons expressed in astrocytes (11)(12)(13). It has been reported that Cx43 hemichannels are sensitive to various stimuli, including osmotic stimulation (19). A connexin hemichannel spans unopposed plasma membrane regions and, following docking with partners, produces a gap junction channel that allows for direct intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Increased detrusor myogenic activity which is an important contributor to BOO induced DO can be induced by many mechanisms including: denervation supersensitivity of cholinergic (muscarinic) receptors (583), increases in purinergic receptor mediated contractile responses as well as expression of purinergic receptors such as P2X1 (75,485), changes in the cell-to-cell communication in detrusor muscles due to upregulation of gapjunction proteins such as connexin 43 (112,253) and increased in the number of interstitial cells (328, 349).…”
Section: Bladder Outlet Obstructionmentioning
confidence: 99%
“…Astrocytes release glutamate through various mechanisms, for example, P2X7 receptor [6] , exocytosis [7,8] , and Cx43 hemichannels [9] . Cx43 is a main connexin protein expressed in astrocytes [10][11][12] and is sensitive to various stimuli including osmotic stimulation [13,14] .…”
Section: Introductionmentioning
confidence: 99%